Phenotypic characterisation of four naked neck chicken ecotypes indigenous to Pakistan - M Shafiq; A Ahmad; H Khaliq; ZM Iqbal; B Siddique; MI Ullah; MF Khalid; F Ali; MT Khan; S Aslam; R Mustafa; U Farooq; et al. (South African Journal of Animal Science)
This study characterised four naked neck chicken phenotypes (black, white-and-black, light brown, and dark brown) at 20 weeks of age, based on both qualitative and quantitative traits. A total of 320 birds were evaluated, with 40 males and 40 females per phenotype. Qualitative traits assessed included head shape, comb type, wattle size, plumage pattern, shank colour, spur presence, and number of toes. Quantitative traits measured included neck length, keel length, wingspan, shank length, shank circumference, drumstick length, drumstick circumference, and body length. Both sexes of all phenotypes exhibited a plain head and a single comb. Wattle size varied by sex, being medium-sized in females and highly developed in males. Feathers in the breast, wing bow, wing bar, wing bay, saddle, and tail areas most commonly had a plain pattern, followed by stippled, pencilled, and laced patterns. Shank colouration differed between the sexes, with males most commonly having yellow shanks, followed by grey, off-white, and green shanks. In contrast, females predominantly had grey shanks, followed by yellow, green, and off-white shanks. Among the phenotypes, white-and-black, light brown, and dark brown chickens exhibited the highest frequency of yellow shanks, while grey shanks were most commonly found in black birds. Males were significantly larger than females for most morphometric traits. Additionally, the light brown and dark brown phenotypes exhibited higher values for quantitative traits than the black and white-and-black phenotypes. All birds of the naked neck phenotype, regardless of sex, had four toes, normal spurs, and tufted feathers on the ventral neck region above the crop.